PERBANDINGAN METODE DESTRUKSI BASAH SISTEM TERBUKA DAN TERTUTUP TERHADAP ANALISIS LOGAM TIMBAL (Pb) DALAM SAMPEL TANAH PADA DAERAH BEKAS PERTAMBANGAN DI SAMARINDA DENGAN AAS - Suci Andriyaningrum; Bohari Yusuf; Rahmat Gunawan (PROSIDING SEMINAR KIMIA, 2018)
Study of the comparison wet destruction methods open and closed systems to the analysis of lead metal (Pb) in soil samples at the former mining site in Samarinda with AAS has been done. The resultant destruction solution was obtained from wet destruction with open and closed systems with temperature and time variation using concentrated HNO3 acid solvent and aqua regia acid. The resultant destruction solution obtained was dissolved with aquadest and tested by Atomic Absorption Spectrophotometer at wavelength 283.3 nm. The result obtained in this research is the concentration of lead metal (Pb) that contained in the soil samples at the former mining site in Samarinda are 13.565 mg/kg with recovery percentage of 100.53% in wet destruction closed methods with the use of concentrated HNO3 acid at temperature 250°C during 2 hours and 15.723 mg/kg with recovery percentage of 100.48% in wet destruction closed methods with the use of concentrated HNO3 acid at temperature 250°C during 3 hours. Keywords: Wet destruction methods, lead metal (Pb), concentrated HNO3, aqua regia, Atomic Absorption Spectrophotometer.